2008
DOI: 10.1095/biolreprod.108.069831
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of the Luteinizing Hormone Surge in Middle-Aged Female Rats by Altering the Balance of GABA and Glutamate Transmission in the Medial Preoptic Area1

Abstract: Hypothalamic glutamate and GABA neurotransmission are involved in the ovarian hormone-induced GnRH-LH surge in rodents. We previously reported that middle-aged rats have significantly less glutamate release in the medial preoptic area than young rats on the day of the LH surge. The present study tested the hypothesis that the delayed and attenuated LH surge in ovariohysterectomized, middle-aged rats primed with ovarian steroids results from reduced hypothalamic glutamate and increased GABAA neurotransmission. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 81 publications
7
40
0
1
Order By: Relevance
“…Moreover, the net effect of decreased GABA turnover might be enhanced synaptic GABA. This possibility is consistent with a recent report by Neal-Perry et al (2008) who showed by microdialysis that GABA release in the POA was increased in middle-aged compared to young ovariectomized, hormone-primed rats.…”
Section: Gamma-aminobutyric Acid (Gaba) and The Hpg Axissupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, the net effect of decreased GABA turnover might be enhanced synaptic GABA. This possibility is consistent with a recent report by Neal-Perry et al (2008) who showed by microdialysis that GABA release in the POA was increased in middle-aged compared to young ovariectomized, hormone-primed rats.…”
Section: Gamma-aminobutyric Acid (Gaba) and The Hpg Axissupporting
confidence: 93%
“…These data suggest a change in the synthesis of GABA such that the rhythmicity of its release, important to the timing of the pre-ovulatory surge, is interrupted, thus providing one explanation for the alteration of this mechanism during the aging transition, contributing to an attenuation of the GnRH/LH surge. Consistently, the important study of Neal-Perry et al (2008) confirms that pharmacological blockade of GABA A Rs with bicuculline in middle-aged rats mitigates the attenuation of the steroid-induced LH surge.…”
Section: Gamma-aminobutyric Acid (Gaba) and The Hpg Axissupporting
confidence: 62%
See 1 more Smart Citation
“…Intravenous injection of NMDA increases LH release in intact rhesus macaques (191). Early work measuring glutamate release associated with the LH surge in rats observed no difference in glutamate levels in the preoptic area in OVXϩE animals (192), but subsequent studies have observed increases in glutamate release in the preoptic area during the LH surge in OVXϩE and OVXϩEϩP models (193)(194)(195), and that these surge-associated changes are attenuated in middle-aged, reproductively senescent animals (196,197). Blockade of either NMDA or AMPA glutamate receptors blocks the LH surge in rats (198 -200).…”
Section: A Glutamatementioning
confidence: 99%
“…In intact rats, however, bicuculline was observed to have no effect on the LH surge in one study (220) but advanced the peak of the LH surge by 3 h in subsequent experiments (222). In middleaged OVXϩEϩP rats, which show an attenuated LH surge, extracellular GABA levels in the preoptic area are increased, and bicuculline infusion in the preoptic area increases LH levels (196). Together, these studies suggested that GABA exerts an inhibitory effect on GnRH/LH release, although antagonism of endogenous GABA levels yielded conflicting data.…”
Section: Effects Of In Vivo Gaba Manipulationsmentioning
confidence: 99%